Analisis Arca Dewi Parwati Menggunakan Teori Bahasa Rupa - Dwi Jaya Arisyana; Apsari Dj. Hasan (Pixel :Jurnal Ilmiah Komputer Grafis, 2024)
This analysis uses the Wimba Method and Visual Language Expression System to examine the visual language of the Goddess Parwati statue. Using a qualitative descriptive research method with a historical background to obtain a description of the creation that is appropriate to the period of its creation. Viewed from the visual language approach, several general things are obtained regarding the Goddess Parwati statue, namely: (1) Iconography aspect: identifying and describing all elements of the Goddess Parwati statue; (2) Historical aspect: The Goddess Parwati statue was discovered in the 14th century. The initial location of the discovery was at the BHRE Kahuripan Site, Panggih Village, Trowulan District, Mojokerto Regency, East Java. (3) Visual language aspect: Seen from the combination of naturalistic-stylized depiction methods using decorative methods. The data analysis model used is an interactive model analysis carried out by collecting data, reducing data, presenting data, and drawing conclusions/verifying data. The study of the contents of the wimba shows that there are various types of jewelry depicted on the Goddess Parwati statue as supporters of the statue's identity. Keywords: Visual Language, Statue of Goddess Parvati, Iconography, Wimba and Phraseology, Qualitative Descriptive Method